PENGGUNAAN MEDIA PEMBELAJARAN VIDEO DALAM MENINGKATKAN PEMAHAMAN MATERI PEMBELAJARAN IPA TENTANG PEREDARAN DARAH MANUSIA KELAS V DI MI YA BAKII PLANJAN - Muntafingah (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
Low science learning achievement is a problem in class V of MI Ya BAKII Planjan. This is due to the low understanding of students in learning science and the lack of selection of appropriate learning media, especially on material on Human Blood Circulation. Therefore, the researcher conducted this PTK with the aim of finding out how to use video learning media in improving the understanding of science learning materials about human blood circulation in grade 5 at MI Ya BAKII Planjan. The type of research used is Classroom Action Research (PTK) with a cycle model which is carried out in semester 1, namely in October-November 2021. There are two cycles with a total of 22 students. The data collection technique is by test, observation, and documentation. The result of this study is that the use of video learning media in the science subject of Human Circulation material class V at MI Ya BAKII Planjan is proven to increase students' understanding of the material. This can be seen from the results of the evaluation in each cycle. In the initial condition, 9 students or 41% of students completed the course, in cycle 1 there were 11 children or 50% of the students who completed the course, and in cycle 2 there were 19 children or 86% of the students with a total of 22 children. The data shows that from the initial learning before using the video learning media, students who completed it were only 9 children. After using video learning media in cycle 1, the number of students who completed the program increased to 11 children. And in cycle 2 it increased again to 19 students who completed. Thus, each cycle has increased in terms of understanding and mastery of learning materials. Keywords : Video Learning Media, Science Learning